Nutritional knowledge, anthropometric profile, total cholesterol and motivations in vegetarians and non-vegetarians - Saintila, Jacksaint; Lozano López, Tabita E.; Calizaya-Milla, Yaquelin E.; Huancahuire-Vega, Salomón; White, Michael (Nutrición Clínica y Dietética Hospitalaria, 2021)
Background: Research often reports on the anthropometric and biochemical profile of vegetarians and non-vegetarians, yet few have compared nutritional knowledge in both populations. This cross-sectional study compared nutritional knowledge, anthropometric profile and total cholesterol in vegetarians and non-vegetarians. In addition, the motivations for choosing a vegetarian diet were analyzed. Methods: A registry card and a questionnaire were administered to evaluate sociodemographic, anthropometric, total cholesterol, nutritional knowledge and motivation data of the vegetarians. Data were analyzed using Chi-square and t-student tests, considering a significance level of 5%. Results: No significant difference was found in the level of nutritional knowledge of the two groups. In addition, a sufficient score was not observed in either group (>80 %). Vegetarians had significantly lower average weight, body mass index (BMI) and waist circumference (WC) compared to non-vegetarians (59.948 ± 8,923 kg vs. 64.362 ± 12.272 kg, p=0.017), (23.22 ± 3.026 kg/m2 vs. 25.152 ± 3,373 kg/m2, p<0.01) and (78.435 ± 10.883 cm vs. 86.207 ± 13.662 cm, p<0.01), respectively. Total cholesterol concentration was significantly lower in vegetarians (166.307 ± 26.139 mg/dL vs. 189.138 ± 38.451 mg/dL, p<0.01). The "health benefits" were the main motivations to opt for vegetarianism (32.3%). Conclusions: Vegetarians presented a better anthropometric profile and lower levels of total cholesterol. However, there were no differences regarding knowledge levels. The highest proportion of vegetarian’s report choosing the vegetarian lifestyle for health reasons.